VD_FINDINFO HC / 2010 / 314 vom 7. April 2010 - VD Tribunal cantonal (2010)
SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, FIXATION DE LA PEINE, POUVOIR D'APPRÉCIATION | 43 CP, 47 CP, 415 CPP, 431 al. 2 CPP